Prediction Modeling of Torque in End-milling - K., Kadirgama; M. M., Noor; M. R. M., Rejab; M. M., Rahman; M. S. M., Sani; R. A., Bakar; N. M. Zuki, N. M. (WIT Press, 2010)
This paper presents the development of mathematical models for torque in end-milling of AISI618 using coated carbides cutting tool. Response surface method was use to predict the effect of torque in the end-milling. From the model, the relationship between the manufacturing process factors including the cutting speed, feed rate, axial depth and radial depth with the torque can be developed. The effect of the factors can be investigated from the equation developed for first order to fourth order model. The acquired results show that the torque increases with decreases of the cutting speed and increases the feed rate, axial depth and radial depth. It found that the second order is more accurate based on the analysis of variance (A&OVA) and the predicted torque results is closely match with the experimental results. Third-and fourth-order model generated for response to investigate the 3- and 4-way interaction between the factors. The third and fourth order model show that 3- and 4-way interaction found less significant for the variables.